Rules of Plant Species Ranges: Applications for Conservation Strategies - Shay, Jackie E.; Pennington, Lillie K.; Mandussi Montiel-Molina, Jorge A.; Toews, Daniel J.; Hendrickson, Brandon T.; Sexton, Jason P. (Frontiers in Ecology and Evolution, 2021)
Earth is changing rapidly and so are many plant species’ ranges. Here, we synthesize eco-evolutionary patterns found in plant range studies and how knowledge of species ranges can inform our understanding of species conservation in the face of global change. We discuss whether general biogeographic “rules” are reliable and how they can be used to develop adaptive conservation strategies of native plant species across their ranges. Rules considered include 1) factors that set species range limits and promote range shifts; 2) the impacts of biotic interactions on species range limits; 3) patterns of abundance and adaptive properties across species ranges; 4) patterns of gene flow and their implications for genetic rescue, and 5) the relationship between range size and conservation risk. We conclude by summarizing and evaluating potential species range rules to inform future conservation and management decisions. We also outline areas of research to better understand the adaptive capacity of plants under environmental change and the properties that govern species ranges. We advise conservationists to extend their work to specifically consider peripheral and novel populations, with a particular emphasis on small ranges. Finally, we call for a global effort to identify, synthesize, and analyze prevailing patterns or rules in ecology to help speed conservation efforts.